PEMANFAATAN BATU PECAH ASAL BUKIT KENDI DAN PASIR SUNGAI LEMATANG KABUPATEN MUARA ENIM SEBAGAI MATERIAL LAPIS PERMUKAAN JALAN (HRS-WC) - , Yusrizal ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Utilization of local materials continue to be studied and developed as a local resource. Local materials in the form of Lematang river sand and Bukit Kendi crushed stone is very supportive to the development of road infrastructure in the region especially Muara Enim regency. The goal of research on the utilization of Bukit Kendi crushed stone and Lematang river sand as road surface material layer (surface course) was to determine the material characteristics as the surface layer of the road based on the Marshall test and Indirect Tensile Strength, knowing the characteristics of asphalt and aggregate mixture as a layer of road surface type HRS-WC and know the composition of a mixture optimal HRS-WC. In this study the materials used are coarse aggregate Bukit Kendi crushed stone, fine aggregate Lematang river sand, and fine aggregate Bukit Kendi crushed stone, while the filler from Celereng, tested with 4 (four) variation of mixed types of pavement HRS-WC. The main testing conducted in this study using testing methods Marshall and indirect tensile strength test. From the standard Marshall test results obtained value of Optimum Asphalt Content (OAC) for variations in 2 amounting to 7.45%, a variation 2 of 7.0%, variation 4 of 7.7%. For the density value, VFA, VIM, VMA, Stability, flow and Marshall Quotient (MQ) variations in the mixture 2 is 2.265 g / cc